Neuroendocrine background of climacteric syndrome on the basis of serum serotonin and neuropeptide Y level assessment in postmenopausal women - Warenik-Szymankiewicz, Alina; Męczekalski, Błażej; Słopień, Radosław (Menopause Review/Przegląd Menopauzalny, 2003)
The aim of this study was to determine serum levels of serotonin and neuropeptide Y (NPY) in postmenopausal women with climacteric symptoms and to assess the relationship between serum levels of serotonin and NPY and the presence of climacteric symptoms. We studied 41 postmenopausal patients attending the Clinic of Gynecological Endocrinology, University of Medical Sciences, Poznań because of climacteric complaints. In the study group the severity of climacteric symptoms was assessed using the Kupperman index. Serum 17beta-estradiol, follicle stimulating hormone (FSH), serotonin and NPY concentrations were measured by radioimmunoassay. The mean serum serotonin concentration in the group of patient with mild climacteric syndrome was 97.7 ng/ml (SD±16.6 ng/ml), and in the group of patients with moderate and severe climacteric syndrome was 36.2 ng/ml (SD±24.1 ng/ml). The difference between two groups was statistically relevant (Mann Whitney test: p<0.05). The mean serum NPY concentration in the group of patient with mild climacteric syndrome was 16.9 ng/ml (SD±4.1 ng/ml), and in the group of patients with moderate and severe climacteric syndrome was 19.9 ng/ml (SD±11.1 ng/ml). The difference between two groups was not statistically relevant (t-Test: p<0.05). The difference in serum serotonin and NPY concentration between patients with a climacteric symptom and without such a symptom was not statistically relevant for any of the symptoms (Mann-Whitney test and t-test p<0.05). We concluded that serum serotonin concentration in postmenopausal women is related to severity of climacteric syndrome.